Vaccinating healthcare workers: Level of implementation, barriers and proposal for evidence-based policies in Turkey - Lale Ozisik; Mine Durusu Tanriover; Serdar Altınel; Serhat Unal (Taylor & Francis Group, 2017)
The role of healthcare workers in life-long vaccination is very important in the means of 2 sided infection, rising patient awareness and being a role model for the patients. Numerous organizations publish guidelines for vaccination of HCWs, while healthcare facilities develop vaccination policies according to the accreditation standards. Nevertheless, vaccination rates among HCWs are far below targets. The obstacles to getting vaccinated or recommending vaccination may include rather universal factors such as the vaccine paradox, however in the case of HCWs, probably a different set of factors are included. The aims of this article are to gain an overview of vaccination strategies for HCWs, to assess the coverage rates of HCWs and make in-depth analyses of the potential barriers to vaccination and potential factors to motivate HCWs for vaccination in Turkey and to compare them with the global picture to improve implementation of policies concerning vaccination of HCWs.